First Cretaceous turtle from Antarctica - de la Fuente, Marcelo Saul; Novas, Fernando Emilio; Isasi, Marcelo Pablo; Lirio, Juan Manuel; Nuñez, Héctor J. (Journal of Vertebrate Paleontology)
The James Ross Basin is located on the NE extreme of the Antarctic Peninsula and centered on the James Ross Archipelago (del Valle et al., 1992). This basin accumulated one of the thickest and most complete sedimentary sequences of Lower Cretaceous through Lower Cenozoic ages exposed on the southern hemisphere. One of the paleontologically most productive horizons of the James Ross Basin is the Upper Cretaceous Santa Marta Formation (Olivero et al., 1986), estimated to be Late Coniacian through Latest Campanian on the basis of strontium isotope stratigraphy (McArthur et al., 2000). The Santa Marta beds yielded a diverse assemblage of both marine and terrestrial fossil vertebrates (see overview by Reguero and Gasparini, 2007), including sharks (Clamydoselachidae, Squatinidae), actinopterygian fishes (Aulopiformes Enchodontidae, and Actinopterygii indet.; Richter and Ward, 1990; Kriwet et al., 2006), mosasaurs (Tylosaurinae; Novas et al., 2002), plesiosaurs (Polycotylidae; D´Angelo et al., 2008), and dinosaurs (Ankylosauria; Gasparini et al., 1987; 1996; Olivero et al., 1990). Here we report on a partially preserved chelonioid carapace found in levels of the Santa Marta Formation, thus constituting the oldest-known turtle from Antarctica. The new discovery enlarges the meager fossil record of turtles from this continent, currently restricted to an Eocene demochelyid chelonioid reported from the La Meseta Formation (de la Fuente et al., 1995). Fil: de la Fuente, Marcelo Saul. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina. Museo Municipal de Historia Natural San Rafael - Unidad Asociada al CCT Mendoza; Argentina Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones ...